Philosophical prospective of organisational learning - Turi, Jamshid Ali; Sorooshian, Shahryar; Fatimah, Mahmud; Nawanir, Gusman; Islam, A. S. M. Touhidul (Inderscience Enterprises Ltd., 2019)
This article reviews and evaluates the concepts of the philosophical foundation of the organisational learning. Drawing on established literature in the field of organisational learning, the authors analyse learning from three perspectives - epistemological, ontological and sociological. They argue that how different internal and external phenomenon gives birth to the learning in organisation and how the organisation can benefit utilising them for the better management and productive engagement. The study concludes with some practical suggestions about how organisations can increase their ability to learn.